Efeito da administração da polpa de Juçara (Euterpe edulis mart) em camundongos tratados com dieta hiperlipídica e hipercalórica sobre parâmetros metabólicos, inflamação e permeabilidade intestinal - Silva, Fernanda Pinheiro Da [UNIFESP] (2019)
Obesity is multifactorial disease and one of factor is an ingestion of hypercaloric diet rich in fat and ultra-processed food and poor in micronutrients and fiber. The ingestion of fruits, vegetable and leguminous is emphasize by benefits and proprieties to promote health. In this sense, some food rich in bioactive compounds are studied to prove their capacity to decrease the deleterious metabolic effect promoted by refined sugar and fat rich-diet. The goal of this study was evaluated the effect of jucara (Euterpe edulis Mart) supplementation, fruit rich in fiber and bioactive compound, majority anthocyanin, on metabolism, inflammation, and also, the intestinal permeability and fecal bacterial microbiome characterization in obese mice induced by hypercaloric and hyperlipidic diet. Swiss mice were treated with hyperlipidic and hypercaloric diet supplemented or not with 0.5% and 2% of jucara pulp for sixteen weeks. Body composition and metabolic parameters were analyzed. Pro and anti-inflammatory cytokines were evaluated in different tissues. Proteins of TLR-4 pathway and tight junctions were quantified in the colon. Colon fecal bacterial microbiome characterization was done. The results showed that sixteen weeks treatment with hyperlipidic and hypercaloric diet was efficient to developing obesity in mice, changing both body composition and metabolism. On the other hand, the jucara supplementation did not alter statistically these parameters. We observed a physiological difference, decreasing the pro-inflammatory cytokines concentration in the epididymal adipose tissue depot, more evident in the 0.5% group compared to no supplemented one. Jucara supplementation decreased the pro-inflammatory cytokines and TLR-4 protein content and did not modify the tight junction proteins. The main composition of bacteria of the colon belongs to Firmicutes and Bacteroidetes filo and the jucara did not modify this pattern. The ratio Firmicutes/Bacteroidetes (F/B) was 0.87 in control group, indicating that Bacteroidetes abundance was higher than Firmicutes in lean animals. The opposite was observed in all hyperlipidic and hypercaloric diets, being the F/B ratio higher in the hypercaloric group (1.64) and lower in the groups treated with juçara pulp, at concentrations of 0.5 and 2% (1.17 and 1.58, respectively). The most expressive result was observed in the Firmicutes filo, specifically in the Erysipelotrichia class. The hyperlipidic diet increased the relative abundance compared to control group and jucara normalized to a control pattern. The hyperlipidic and hypercaloric diet supplemented with jucara for sixteen weeks did not modify the general metabolic aspects, but decreased the pro-inflammatory profile in the epididymal adipose tissue depot and colon. The exploratory analysis of the colon fecal bacterial microbiome was done and futures analysis of correlation with the metabolic and inflammatory parameter and the microbioma content could show the restrict relation between the intestine and the whole body metabolism.